Volume 8: Microturbines, Turbochargers and Small Turbomachines; Steam Turbines 2015
DOI: 10.1115/gt2015-43555
|View full text |Cite
|
Sign up to set email alerts
|

On-Line Prediction of Temperature and Stress in Steam Turbine Components Using Neural Networks

Abstract: Considered here are Nonlinear Auto-Regressive neural networks with exogenous inputs (NARX) as a mathematical model of a steam turbine rotor used for the on-line prediction of turbine temperature and stress. In this paper on-line prediction is presented on the basis of one critical location in a high pressure steam turbine rotor, according to power plant common measurements, i.e., turbine speed, turbine load as well as steam temperature and pressure before turbine control valve. In order to obtain neural networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…For the analysis of the heating method, a part of the high pressure (HP) turbine shaft was selected, in which [1,2] critical stress has been found due to the phenomena described above. The location of its occurrence is the bottom of the groove for fixing the blades.…”
Section: Object Of Investigationsmentioning
confidence: 99%
See 2 more Smart Citations

Archives of Thermodynamics

Dominiczak,
Drosińska-Komor,
Rzadkowski
et al. 2020
“…For the analysis of the heating method, a part of the high pressure (HP) turbine shaft was selected, in which [1,2] critical stress has been found due to the phenomena described above. The location of its occurrence is the bottom of the groove for fixing the blades.…”
Section: Object Of Investigationsmentioning
confidence: 99%
“…On line information regarding relative stress allows to start up the steam turbine in the shortest possible time and in the same time maintain requested design life of the turbine. It might be concluded that the steam turbine lifetime consumption of the steam turbine due to thermal low cyclic fatigue is minimized for given preconditions as turbine initial condition and thermal boundary conditions during the turbine startup [1,2]. The course of start-up planning is also relevant for the process of turbine start-up.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation

Archives of Thermodynamics

Dominiczak,
Drosińska-Komor,
Rzadkowski
et al. 2020
“…Optimization of the technological or operation parameters of rotating machines is needed to meet rising demands put on their design or accomplish the technological processes. Du et al [31] and Dominiczak et al [32] reported on the optimization of the start-up procedure of large steam turbines, focusing on heat parameters. Saldarriaga and Steffen [33], Mohammadzadeh and Ghoddoosian [34], and Yao et al [35] dealt with balancing the rotors based on the utilization of different optimization methods.…”
Section: Introductionmentioning
confidence: 99%